Controlling the surface roughness of chain-like Pd nanowires by pH values as excellent catalysts for oxygen reduction reaction. (8th March 2019) - Zhang, Yun-Long; Sui, Xu-Lei; Zhao, Lei; Gu, Da-Ming; Huang, Guo-Sheng; Wang, Zhen-Bo
Abstract: The microscopic surface plays a crucial impact on catalytic activity. Herein, the rough-surfaced chain-like palladium nanowires with many steps and inflections are successfully synthesized by a simple one-step reduction by sodium borohydride. The mechanism of bromide ions adsorbing and the oxygen etching to control the growth of chain-like nanowires is investigated. Furthermore, the effect of the pH values of system on the microscopic surface of palladium nanowires, especially on the roughness, is discussed in depth. The nanowires prepared at pH = 11 exhibit rougher surfaces with a diameter of 10–11 nm, and the relevant catalyst has higher electrochemical active area and excellent electrocatalytic performance for oxygen reduction reaction (ORR). Its half-wave potential in 0.5 mol L −1  H2 SO4 solution is 80 mV more positive than Pd nanoparticles, slightly negative than Pt/C and the half-wave potential in 0.1 mol L −1 KOH solution is 50 mV more positive than the Pd nanoparticles, and is almost the same as Pt/C. The research result reported here will have important implications for designing palladium-based catalysts to increase their electrocatalytic ability. Graphical abstract: Image 1 Highlights: The bromide ions adsorbing and oxygen etching controls the growth of nanowires. The pH values of system influences the roughness of Pd nanowires. The chain-like Pd nanowires show the better performance than Pd nanoparticles. The excellent performance results from more active sites of the rough surface.